2009
DOI: 10.1185/03007990902896386
|View full text |Cite
|
Sign up to set email alerts
|

Trends in RA patients’ adherence to subcutaneous anti-TNF therapies and costs

Abstract: ETA users had longer treatment duration, were more likely to adhere to their medication regimen and had lower RA-related pharmacy and RA-related total costs compared with ADA users. These findings must be considered within the limitations of this database analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 28 publications
10
72
1
6
Order By: Relevance
“…This is consistent with previous findings [21]. The positive influence of comorbidity on adherence is also in accordance with other studies [22,23]. Finally, a better mental health status was also associated to medication adherence in at least one other study [11].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous findings [21]. The positive influence of comorbidity on adherence is also in accordance with other studies [22,23]. Finally, a better mental health status was also associated to medication adherence in at least one other study [11].…”
Section: Discussionsupporting
confidence: 93%
“…Demographic (age and gender distribution) and clinical characteristics of the final matched study sample were found to be consistent with those reported by other studies of patients with RA that were conducted using retrospective database analysis. 2,4,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] However, in contrast to other studies where the majority of participants were white, the present study had a majority Hispanic population (53.7%). 31,32,36,37 This was expected, since Hispanics have been reported to account for a significant proportion (≈ 40%) of the Texas population.…”
Section: Medication Effectiveness With the Use Of Tumor Necrosis Factcontrasting
confidence: 42%
“…Adherence seen in this study was lower than has been reported in previous adherence studies that also used administrative claims data (commercial or Medicaid). 2,30,31,36 This may be because of the high Hispanic population (53.7%) in the study sample. Being of an ethnic minority has been associated with poor medication adherence.…”
Section: Medication Effectiveness With the Use Of Tumor Necrosis Factmentioning
confidence: 90%
See 2 more Smart Citations